Assessment of Safety and Probiotic Traits of Enterococcus durans OSY-EGY, Isolated From Egyptian Artisanal Cheese, Using Comparative Genomics and Phenotypic Analyses - Hussein, Walaa E.; Abdelhamid, Ahmed G.; Rocha-Mendoza, Diana; García-Cano, Israel; Yousef, Ahmed E. (Frontiers in Microbiology, 2020)
An Enterococcus durans strain, designated OSY-EGY, was previously isolated from artisanal cheese. In this work, comparative genomic and phenotypic analyses were utilized to assess the safety characteristics and probiotic traits of the bacterium. The comparative genomic analysis revealed that the strain is distantly related to potentially pathogenic Enterococcus spp. The genome was devoid of genes encoding acquired antibiotic resistance or marker virulence factors associated with Enterococcus spp. Phenotypically, the bacterium is susceptible to vancomycin, ampicillin, tetracycline, chloramphenicol, and aminoglycosides and does not have any hemolytic or gelatinase activity, or cytotoxic effect on Caco-2 cells. Altogether, these findings confirm the lack of hazardous traits in E. durans OSY-EGY. Mining E. durans OSY-EGY genome, for probiotic-related sequences, revealed genes associated with acid and bile salts tolerance, adhesion, competitiveness, antioxidant activitiy, antimicrobial activity, essential amino acids production, and vitamins biosynthesis. Phenotypically, E. durans OSY-EGY was tolerant to acidic pH (3.0), and presence of 0.3% bile salts. The bacterium showed adhesion capability to Caco-2 cells, cholesterol lowering effect, DPPH scavenging activity, and showed antimicrobial activity against several Gram-positive pathogenic bacteria. Based on the current work, we propose that E. durans OSY-EGY is a potentially safe strain with desirable probiotic and antimicrobial traits. Thus, the investigated strain could be a promising candidate for several industrial applications.